Poverty trends in Pakistan - Nazli Hina; Edward Whitney; Kristi Mahrt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The official estimates of poverty in Pakistan have shown a remarkable and consistent decline in the poverty headcount during the previous decade. This paper examines trends in poverty between 2001 and 2011 using the official food energy intake and the cost of basic needs approaches, both of which are modified to allow poverty lines to vary over time and space. The latter estimates provide utility-consistent poverty lines through the imposition of revealed preference conditions in maximum entropy adjustments. Evidence from both methods suggests that poverty incidence increased rather than declined as indicated in the official estimates.
Keywords: I32; D12; O53; R20; 330; poverty measurement; utility consistency; spatial variation; Pakistan